Are female offenders underreported compared to male offenders: a German-Greek comparison of crime reporting, rating of offence seriousness and personal experiences of victimisation - Stroh, Michael (European journal on criminal policy and research, 2016)
The difference in official crime statistics between women and men is a constant fact in criminology, but has yet to be explained in a satisfactory way. There are few studies addressing the issue of why this gender gap is larger in registered crime than it is in self-report studies. The study at hand comprises a survey among Greek and German students to examine whether this gap could be attributed to a gender-specific reporting of crime. Participants’ self-reported experiences of victimisation and their rating of the seriousness of offences depicted in case vignettes were used to gain insight into varying tendencies to report a crime depending on the offender’s gender. The act of reporting a crime did not vary gender-specifically.